2014
DOI: 10.1039/c3sm52817k
|View full text |Cite
|
Sign up to set email alerts
|

Total internal reflection spectroscopy for studying soft matter

Abstract: Total internal reflection (TIR) spectroscopy is a widely used technique to study soft matter at interfaces. This tutorial review aims to provide researchers with an overview of the principles, experimental design and applications of TIR spectroscopy to enable them to understand how this class of techniques might be used in their research. It also highlights limitations and pitfalls of TIR techniques, which will assist readers in critically analysing the literature. Techniques covered include attenuated total r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
65
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 212 publications
(270 reference statements)
1
65
0
Order By: Relevance
“…[27,29]. However, the problem appears when T D const and, in particular, when T 1 is required within a wide range of Â-variation together with sharp switching between T 1 and T D 0.…”
Section: Low-pass Filteringmentioning
confidence: 96%
“…[27,29]. However, the problem appears when T D const and, in particular, when T 1 is required within a wide range of Â-variation together with sharp switching between T 1 and T D 0.…”
Section: Low-pass Filteringmentioning
confidence: 96%
“…Recent progress in the field has allowed the inclusion of cryo-probes and the development of electron crystallography (used to determine the structure of several proteins allowing the identification, in some cases, of secondary structure motifs) [97, 98]. Other techniques [91] used to support research related to protein adsorption include capillary electrophoresis [99], mass spectrometry [100, 101] and particle mass spectrometry [102] (to identify and quantify proteins through fragmentation), various vibrational spectroscopictechniques [103, 104] (to study protein/substrate interface and elucidate the biosensing mechanism), UV-Vis spectroscopy [105], Fourier-transform infrared (FTIR) spectroscopy[106, 107] (to analyze sequential and competitive adsorption), circular dichroism (CD) spectroscopy[108, 109] (to investigate the secondary structure of adsorbed proteins), isothermal titration calorimetry [110] (to investigate thermodynamic properties of interactions), surface plasmon resonance (SPR)[37, 111-113] (for quantitation of proteins and kinetic studies but limited to gold or silver surfaces), total internal reflection fluorescence spectroscopy [114] (for determining conformational changes in adsorbed proteins), infrared spectroscopy [115] (to observe protein conformation and load but with limited use in multicomponent protein solutions because of complex spectra), and fluorescence spectroscopy[84, 116] (to observe structural change in protein and protein loading).As their interaction with proteins can lead to spectral shifts in gold nanoparticles(AuNP), various colorimetric assays have been presented to monitor either protein-protein interactions [117] or conformational changes [118]. Additionally, it was recently reported that in the low protein coverage regime, nanoparticle tracking analysis, and differential dynamic light scattering (but not differential centrifugal sedimentation)correlate with the expected plasmon frequency shift of AuNP[119].…”
Section: Techniques To Investigate Protein Adsorptionmentioning
confidence: 99%
“…15 Therefore, TIR Raman spectroscopy lacks the intrinsic surface sensitivity of non-linear optical methods such as SFG. 15 Therefore, TIR Raman spectroscopy lacks the intrinsic surface sensitivity of non-linear optical methods such as SFG.…”
Section: Introductionmentioning
confidence: 99%